2023
DOI: 10.3390/coatings13020304
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Evaluation of the Relationship of Asphalt Binder and Asphalt Mastic via a Modified MSCR Test

Abstract: Asphalt mastic, which consists of an asphalt binder and a mineral filler, provides critical adhesion and viscoelasticity to an asphalt mixture. The rheological response of the asphalt mastic is mainly derived from its asphalt binder. In this study, a simple laboratory test method is proposed to estimate the relationship of asphalt binder and its mastic. Two modified binders (3.5% and 4.0% styrene–butadiene–styrene (SBS) of asphalt binder by mass) were blended with a limestone filler at six different mineral fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…The notion was that the reduction in adhesive forces between the asphalt and geopolymer stemmed from the asphalt binder undergoing liquefaction at elevated temperatures. Conclusions supporting this finding have been drawn in relevant literature [41,42,81].…”
Section: Mscr Tests Results and Rutting Potentialsupporting
confidence: 83%
“…The notion was that the reduction in adhesive forces between the asphalt and geopolymer stemmed from the asphalt binder undergoing liquefaction at elevated temperatures. Conclusions supporting this finding have been drawn in relevant literature [41,42,81].…”
Section: Mscr Tests Results and Rutting Potentialsupporting
confidence: 83%
“…1-14) conducted an MSRP test on different PMBs at high temperatures, where he found that compared to standard criteria, MSCR performed better at differentiating between complex binders. Binshuo Bao et al [105] (p. 304) conducted an MSCR test to investigate the nonlinear and linear viscoelasticity of SBS-modified asphalt binder and its mastic. Danial Nasr et al [106] (p. 127069) conducted an MSCR test to investigate the rheological characteristics of PE-modified asphalt binder, where the authors found improvements in the modified asphalt.…”
Section: Multiple Stress Creep Recovery (Mscr) Testsmentioning
confidence: 99%
“…, 100 s), b is the linear fitting constant, n is the number of stress levels in each loading sequence (n = 6) and CASR is the average composite strain rate of the asphalt mixture. The multiple-stress creep-recovery (MSCR) test is usually used to investigate the hightemperature rheological properties of asphalt binder in recent studies [26,30,31]. During the MSCR test, dynamic loading is applied to the asphalt binder specimens by DSR with controlled stress loading [32].…”
Section: Laboratory Tests 221 Multisequence Repeated Loading Test Of ...mentioning
confidence: 99%